2001
DOI: 10.1144/petgeo.7.s.s65
|View full text |Cite
|
Sign up to set email alerts
|

Integration of production data into reservoir models

Abstract: The problem of mapping reservoir properties, such as porosity and permeability, and of assessing the uncertainty in the mapping has been largely approached probabilistically, i.e. uncertainty is estimated based on the properties of an ensemble of random realizations of the reservoir properties all of which satisfy constraints provided by data and prior geological knowledge. When the constraints include observations of production characteristics, the problem of generating a representative ensemble of realizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 56 publications
0
35
0
1
Order By: Relevance
“…The optimisation scheme that we have chosen is a variant of a Genetic Algorithm, and is described in the third section . We did not concur with the view that Genetic Algorithms veere not an appropriate optimisation method for reservoir characterisation [7] . The next sections examine the effect of variations in the Genetic Algorithm structure and compares our results with other methods .…”
Section: European Conference On the Mathematica Of Oil Recove Ry -Frementioning
confidence: 60%
See 1 more Smart Citation
“…The optimisation scheme that we have chosen is a variant of a Genetic Algorithm, and is described in the third section . We did not concur with the view that Genetic Algorithms veere not an appropriate optimisation method for reservoir characterisation [7] . The next sections examine the effect of variations in the Genetic Algorithm structure and compares our results with other methods .…”
Section: European Conference On the Mathematica Of Oil Recove Ry -Frementioning
confidence: 60%
“…Each method has advantages and disadvantages, but no single method has met with general acceptance by the reservoir engineering community, a review of these methods can be found elsewhere [2] . It has been suggested [7] that Genetic Algorithms would not be a good choice as an optimiser for this problem . Our reasons for selecting the GA are based on four considerations : 1 .…”
Section: Generating a Reservoir Mode Lmentioning
confidence: 99%
“…Gradient methods fall into two classes, depending on the number of derivatives to be calculated [124]. If the number is small, then direct calculation of the objective function gradient is best.…”
Section: Derivative-free Methodsmentioning
confidence: 99%
“…Moreover the number of gradzones that can be used is restricted because of the inefficient gradient simulator methods used to generate sensitivity coefficients. Although Schlumberger Evaluation & Production Services is developing improved automatic history matching software for data integration based on some of our research funded previously by DOE (Oliver et al (2001); Li et al (2003a); Reynolds (2002b, 2003)), the costs of this software will be prohibitive for many independent water saturation (Krocw) is fixed and is not treated as a model parameter when both absolute permeabilities and relative permeability are adjusted during history matching. In cases that Krocw is chosen to be a model parameter, checkbox "Krocw" needs to be checked.…”
Section: Description Of Taskmentioning
confidence: 99%